Abū Rayhān Bīrūnī : danishmand-i pīshahang - Jūzjānī, ʻA. H. Sharʻī (Bayhaqī Kitāb Khparawanah, 1978)
On the life of Muḥammad ibn Ahmad al-Bīrūnī, 973?-1048, with special reference to his contribution to various sciences.